Peningkatan Kapasitas Penyelenggara Pemerintahan Desa dalam Tata Kelola Pemerintahan Desa di Desa Banjaran Kecamatan Maja Kabupaten Majalengka Provinsi Jawa Barat - Rizki Amalia; Melinda Nurcahya Lestari; Maria Ekowati; Ajud Tajudin (Civitas Consecratio: Journal of Community Service and Empowerment, 2025)
This community service activity aims to enhance the capacity of village government administrators in Banjaran Village, Maja District, Majalengka Regency, West Java Province in realizing more effective village governance, particularly in administrative management and the utilization of the Village Information System (SID). The main issues identified include the limited understanding of village officials, the Village Consultative Body (BPD), and other village institutions regarding regulations and administrative procedures, low work motivation, and insufficient information technology competencies, such as computer operation and digital data management. To address these challenges, the assistance activities were carried out using lecture methods, participatory discussions, and hands-on practice in computer use and SID operation. The implementation of the program showed significant outcomes, including improved understanding among village officials regarding their institutional duties and functions, increased motivation and awareness of the importance of professional work ethics, and enhanced basic skills in using SID as a tool to support public services and administrative transparency. Overall, this capacity-building initiative successfully strengthened the capability of village government administrators and is expected to contribute to improving the quality of governance and public service delivery in Banjaran Village.